Terahertz wave radiation from mutually injection locked multi‐element graphene nanoribbon avalanche transit time sources. (4th June 2020) - Acharyya, Aritra
Abstract: Mutual injection locking of multi‐element graphene nanoribbon impact avalanche transit time (G‐IMPATT) sources designed to operate at different millimeter‐wave (mm‐wave) and terahertz frequencies has been studied. Planar circuit is used for implementing the mutual injection locking between adjacent elements of the source operating in parallel‐connected‐power‐combined mode. The static, high frequency and noise simulations of the proposed sources have been carried out by using in‐house simulation codes based on self‐consistent quantum drift‐diffusion model. Results show that mutual injection locking between the adjacent elements forced the sources to oscillate nearly at a single frequency even if significantly high degree of mismatch is present among the elements of the multi‐element oscillators. A minor amount of reduction in power out and insignificant deterioration in the noise performance of the multi‐element G‐IMPATT oscillators have been observed due to the presence of mutual injection locking between the adjacent elements.